TRANSFIGURATION OF NATIONAL HEALTH FINANCING TO RURAL COMMUNITIES: A Case of Pastoro-Nomadic Communities in Marsabit County, Kenya. - MOHAMED DAWE (International Journal of Economics Development Research (IJEDR), 2020)
Health financing is one of the important goals of any government. In Kenya, the government is exerting all effort to ensure its citizens’ health care needs are safeguarded through increased budgeting and putting in place requisite legislative measures. However, like any other developing nation, the dream of equity in accessing health care is not satisfactorily realized due to many challenges. For pastoralist/nomadic communities in the country, who are deemed marginalized in a considerable number of spheres relative to communities subscribing to other subsistence strategies, the solution is far from being hoped for. This research asks the question “how can national health financing be transfigured to suit the need of pastoral-nomadic communities?”. The research adopted descriptive research design to survey household in the four constituencies of Marsabit County. Respondents were selected using random sampling. Structured questionnaire and focused group discussion was used to gather data and using logistic regression. Many of them do not have a formal education and hence formal employment to enable them have consistent income to pay for their health cover forcing them depend on donors. It was recommended that education should be enhanced so as to upscale the enrolment to health insurance. Further, they should be encouraged to join to a welfare group so as to access finances for payment of insurance subscription. The government should diversify mode of payment and also mobilize resources that will be used to help the poor pay for their health financing need.